Sympathetic Neurostress Drives Osteoblastic Exosomal MiR‐21 Transfer to Disrupt Bone Homeostasis and Promote Osteopenia. Issue 3 (16th December 2021) - Hu, Cheng‐Hu; Sui, Bing‐Dong; Liu, Jin; Dang, Lei; Chen, Ji; Zheng, Chen‐Xi; Shi, Songtao; Zhao, Na; Dang, Min‐Yan; He, Xiao‐Ning; Zhang, Li‐Qiang; Gao, Ping‐Ping; et al.
Abstract: Innervation and extracellular vesicle secretion co‐exist in the local tissue microenvironment for message transfer, but whether they are interconnected to regulate organ homeostasis remains unknown. Sympatho‐adrenergic activation is implicated in stress‐induced depression and leads to bone loss, but the mechanisms and therapeutics are incompletely elucidated. Here, it is revealed that sympathetic neurostress through the β1/2 ‐adrenergic receptor (β1/2‐AR) signaling triggers the transcription response of a microRNA, miR‐21, in osteoblasts, which is transferred to osteoclast progenitors via exosomes for dictating osteoclastogenesis. After confirming that miR‐21 deficiency retards the β1/2‐AR agonist isoproterenol (ISO)‐induced osteopenia, it is shown that the pharmacological inhibition of exosome release by two clinically‐relevant drugs, dimethyl amiloride and omeprazole, suppresses osteoblastic miR‐21 transfer and ameliorates bone loss under both ISO and chronic variable stress (CVS)‐induced depression conditions. A targeted delivery approach to specifically silence osteoblastic miR‐21 is further applied, which is effective in rescuing the bone remodeling balance and ameliorating ISO‐ and CVS‐induced osteopenias. These results decipher a previously unrecognized paradigm that neural cues drive exosomal microRNA communication to regulate organ homeostasis and help to establish feasible strategies to counteract bone loss under psychological stresses. Abstract : It was discovered that sympatho‐adrenergic cues provoke transcription response of miR‐21 in osteoblasts, which is transferred via exosomes to dictate osteoclastogenesis and disrupt bone homeostasis. It is further shown that pharmacological inhibition of exosome release by clinically‐relevant drugs, dimethyl amiloride or omeprazole, and targeted delivery of antagomir‐21 to osteoblasts are effective in ameliorating osteopenias against isoproterenol and depression stresses.